Comparative Analysis of Entrepreneurship Management in Financial Management in the Educational Environment of the Kapedi, Sumenep - Wahyu, Wahyu Maulana; Asas, Istianah Asas; Marsum, Marsum (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This research is motivated by the importance of entrepreneurship for every group, especially in the educational environment, to encourage a better economy in the future. Where this will have an impact on financial management which is one of the goals of entrepreneurship itself, namely boosting the economy. The problem faced is how to implement effective entrepreneurship management so that it has an impact on good financial management. The aim of this research is to analyze the application of entrepreneurship management which has an impact on financial management in the educational environment. The method in this research is quantitative comparative where the subjects are students in the educational environment of SMKS DARUN NAJAH, samples taken using purposive sampling techniques. Data collection used field observations and interviews. The analysis technique uses a 2 independent sample t test. The research results show that from the results of the 2 independent sample t test, there is a significant difference in sales of soy milk and bread products between class 2 and class 3 students; the normality assumption is not met; From the results of the Mann-Whitney test, there is a significant difference in sales of soy milk and bread products between class 2 and class 3 students